“More beautiful and more terrible than anything anyone has ever said”: 9/11, BLM, and the creation of an American identity - Batt, Joanna; Joseph, Michael L.; Brown, Anthony L. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
We contend that September 11th and the Black Lives Matter movement acted as critical moments that challenged earlier notions of the American identity and the false pretenses of a racially, religiously, and culturally equitable United States. Using theoretical lenses of double consciousness and cultural memory, we further that the way newspapers present narratives of these events emphasizes how the memories of a country and who they think they are fluctuate and change throughout time. We end with implications for social studies spaces that seek to explore 9/11 and the Black Lives Matter movement’s impact on American national identity, and/or hope to critique how memories shaped by media outlets like newspapers reinscribe or counter previous notions of the American national identity.